2016
DOI: 10.1097/sle.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Spigelian Hernia Repair: A Systematic Review

Abstract: There are a number of laparoscopic techniques available to the surgeon repairing a SH. Overall, laparoscopic repair of the SH is a safe and acceptable method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
0
28
0
2
Order By: Relevance
“…Literature is sparse, including only a limited number of patients. Three reviews, one RCT and one prospective case series were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Literature is sparse, including only a limited number of patients. Three reviews, one RCT and one prospective case series were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Spigelian hernias can present as acute small bowel obstructions [15, 21] even of the colon [22]. Most Spigelian hernias present a localised hernia, or as local pain with or without a hernia sac [1520].…”
Section: Resultsmentioning
confidence: 99%
“…Most Spigelian hernias present a localised hernia, or as local pain with or without a hernia sac [1520]. Symptoms however can also be insidious and vague.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations